2000
DOI: 10.1159/000007804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ecabet Disodium, a Novel Locally-Acting Antiulcer Drug, on Epithelial Restitution following Injury by Hypertonic NaCl in Bullfrog Stomach in vitro

Abstract: Background: The antiulcer drug ecabet 2Na (12-sulfodehydroabietic acid disodium salt) exhibits a gastroprotective activity, mainly through a local action, involving endogenous prostaglandins (PGs) and nitric oxide (NO). In the present study, we examined the effect of ecabet on the epithelial restitution of the bullfrog gastric mucosa in vitro following injury by hypertonic NaCl. Methods: Bullfrog fundic mucosa was mounted in an Ussing chamber. The tissue injury was induced by exposure of the mucosa to 1.25 M N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…ES, a dehydroabietic acid derivative from pine resin, has been used clinically in the treatment of gastritis and gastric ulcer, and is believed to exert its effects through various mechanisms [20][21][22][23][24] . ES binds directly to the gastric mucosa, thereby protecting the mucosa against ethanol binding, and it has been shown to inhibit pepsin activity in rat and human gastric juices.…”
Section: Asaoka D Et Al Reflux Esophagitis and Upper Esophagusmentioning
confidence: 99%
“…ES, a dehydroabietic acid derivative from pine resin, has been used clinically in the treatment of gastritis and gastric ulcer, and is believed to exert its effects through various mechanisms [20][21][22][23][24] . ES binds directly to the gastric mucosa, thereby protecting the mucosa against ethanol binding, and it has been shown to inhibit pepsin activity in rat and human gastric juices.…”
Section: Asaoka D Et Al Reflux Esophagitis and Upper Esophagusmentioning
confidence: 99%
“…Ecabet is a locally acting agent with low absorption, showing a high affinity for the gastric mucus (1,2). Mechanisms of action have been reported as follows: it enhances gastric epithelial restitution, facilitates mucus synthesis and secretion, increases gastric mucosal blood flow and bicarbonate secretion, enhances gastric mucosal prostaglandin E 2 production, and inhibits gastric pepsin and pepsinogen activity (3)(4)(5). It was recently reported that ecabet enema showed a therapeutic effect in some patients with ulcerative colitis (6), but little is known about the mechanism of this effect by ecabet enema.…”
mentioning
confidence: 99%
“…Furthermore, the decreased fluid secretion by indomethacin was significantly antagonized by the concurrent administration of NOR‐3. In addition, nitric oxide has been shown to expedite epithelial restitution in the stomach 42 , . 43 This nitric oxide‐mediated process might also reduce the bacterial invasion by repairing the injured epithelium in the small intestine.…”
Section: Discussionmentioning
confidence: 99%